EMPOWERMENT OF VILLAGE EQUIPMENT THROUGH NONFORMAL EDUCATION APPROACH IN THE FRAMEWORK OF POVERTY REDUCTION IN THE VILLAGE - Wahyudi, Sigit (International Journal of Multidisciplinary Research and Literature, 2022)
This research aims to empirically describe the empowerment of village devices through a non-formal education approach to solve the problem of poverty in the village. Poverty is an old problem that never ends, where various efforts are made but poverty is still stuck. Poverty is not only in the village but also in the city. This problem needs to be understood based on empirical data or experience. The study focused on poverty in villages with different characteristics than the city's contemporaries.  Poverty in the village cannot be overcome personally by the poor people themselves, but rather the need for the involvement of others, especially village devices that do have duties and responsibilities to help the government at the village level, including helping poverty alleviation in the village. This paper was developed based on the results of qualitative research and literature studies (literary research) so that this paper is an integration of field findings and theories. The results showed that village empowerment is done through programmatic and continuous training to help poor people out of poverty independently. Empowerment of village devices is carried out gradually and continuously by developing training materials around strategies to solve the problem of poverty in the village. From implementing this training, village devices can compile and implement various poverty alleviation programs in the village efficiently and effectively